Application of Indocyanine Green During Arteriovenous Malformation Surgery: Evidence, Techniques, and Practical Pearls - Foster, Chase H.; Morone, Peter J.; Tomlinson, Samuel B.; Cohen-Gadol, Aaron A. (Frontiers in Surgery, 2019)
Indocyanine green (ICG) is a fluorescent molecule that enables visualization of hemodynamic flow through blood vessels. Its application to the resection of arteriovenous malformations (AVMs) did not occur until 2007. Since then, industry leaders have rapidly integrated this optical technology into the intraoperative microscope, and the use of ICG videoangiography (VA) has since become routine in AVM surgery among some academic centers. A number of case series have been published since the introduction of ICG VA to AVM neurosurgery. These early reports with small sample sizes were largely qualitative, assigning to the technology “usefulness” and “benefit” scores as perceived by the operators. This lack of objectivity prompted the development of FLOW 800 software, a proprietary technology than can quantify relative fluorescence intensity under the microscope to generate color maps and intensity curves for ad hoc and post hoc analyses, respectively. However, subsequent case series have done little to quantify the effect of ICG VA on outcomes. The available literature predominately concludes that ICG VA, although intuitive to deploy and interpret, is limited by its dependence on direct illumination and visualization. The subcortical components of AVMs therefore represent a natural challenge to ICG-based flow analysis; the scope of ICG VA has been limited to AVMs with a high proportion of superficial angioarchitecture. As a result, digital subtraction angiography has remained the gold standard for confirming AVM obliteration. In this review, we provide an overview of the existing literature on ICG VA in AVM resection surgery. In addition, we describe our own experiences with ICG VA and AVMs and offer the senior author’s surgical pearls for optimizing the marriage of fluorescence flow technology and AVM resection surgery.